Análisis del uso de plataformas digitales sociales en Majestad Televisión de la ciudad de Santo Domingo durante el periodo 2019-2021 - Bimboza Napa, Gilda Alexandra (2024)
ABSTRACT: The exposition of the research project called “ANALYSIS OF THE USE OF SOCIAL DIGITAL PLATFORMS IN MAJESTY TELEVISION OF THE CITY OF SANTO DOMINGO DURING THE PERIOD 2019-2021”, was elaborated with the purpose of understanding and knowing the process that information entails in the medium of traditional television communication to be published in digital platforms. In the development of this research, we worked with different methods, among them: analytical method, field method, scientific method, descriptive method and bibliographic - documentary method. In addition, it is qualitative in nature, where there was no need for the application of sample and population. We proceeded to the analysis of news articles, where we reviewed the use and type of journalistic genres used. The techniques that were used in this research project were: documentary review, content analysis, interview, and observation, where each technique proceeds with its specific instrument. Social digital platforms such as: Facebook, Instagram, Twitter, YouTube, and the Website were analyzed, considering each platform separately because the media outlet did not publish the same content on all platforms. In addition, an interview is conducted with Majestad Tv's production assistant, Tnlgo. Andrés Hurtado, the news director of “Majestad TV”, Mr. Paúl Zea, as well as an expert in communication and digital marketing, Dr. José Rivera. Keywords: Digital platforms, Majestad TV, traditional media, informative notes.